Building RESTful Web Services with .NET Core : Developing Distributed Web Services to improve scalability with .NET Core 2.0 and ASP.NET Core 2.0. - Aroraa, Gaurav (Packt Publishing, 2018)
REST is an architectural style that tackles the challenges of building scalable web services. In today's connected world, APIs have taken a central role on the web. APIs provide the fabric through which systems interact, and REST has become synonymous with APIs. The depth, breadth, and ease of use of ASP.NET Core, makes it a breeze for ...